Sumang Language Form in Gayo Tribe Society - Alfi Syahrin; Simaharani Simaharani; Usman Usman; Hasan Hasan (Edumaspul: Jurnal Pendidikan, 2023)
The aim of this research is to describe the forms of the Sumang language in community implementation in the Bener Kelipah Utara community, Bener Kelipah District, Bener Meriah Regency. This research uses a qualitative descriptive method using sociolinguistic studies. The data in this research are spoken words, sentences spoken by speaker 1 and speaker 2, while the data source is the conversation of speaker 1 and speaker 2 in everyday life. The data collection technique in this research uses the listening method followed by the free, skillful listening technique, recording technique and note-taking technique. The data analysis technique used is the matching technique with the power to select the determining elements and the comparison technique to equate and the comparison technique to differentiate. Based on the research results, 4 data were obtained which included various forms of Sumang. The results of this research show that the language attitudes of the people of Bener Kelipah Utara, Bener Kelipah subdistrict, Bener Meriah Regency are classified as negative language and there are 4 types of Sumang, namely Sumang, namely Sumang Perceraken (prohibition of words), Sumang Kenunulen (prohibition of sitting), Sumang Peangkaten (prohibition of travel) , and Sumang Penengonen (prohibition of sight). As a community of the Gayo tribe, especially the people of Bener Kelipah Utara, Bener Kelipah sub-district, Bener Meriah Regency who have Sumang customs as rules or procedures in life, these Sumang customs should be maintained and preserved in social life.